Stimulating Business and Employment in Yemen - Assaf, Nabila (World Bank, Washington, DC, 2013)
Yemen is at a crossroads. Two years after popular unrest led to the ousting of the former president, there is now a coalition government, and the beginnings of a national political transition. March 2013 saw the launch of the National Dialogue Conference (NDC) that has brought together political and civil society actors from across the spectrum to formulate a constitution and bring closure not only to the unrest that began in 2011, but to decades of unresolved grievances and conflicts within Yemen. Expectations are high and much is riding on the outcome of the NDC, not least of which is the future direction of the Yemeni economy. As in most developing countries, the Yemeni private sector consists predominantly of micro, small, and medium enterprises (MSMEs) - over 97 presentage of firms (about 290,000 in number) have less than 25 employees with total estimated employment of over 600,000 workers, including approximately 30,000 women. The inclusion of these MSMEs in Yemen's economic recovery is critical for social stability as they represent a significant portion of the jobs outside the public sector and a significant source of income for segments of the Yemeni population. Even more crucially, they also represent an important source of potential future job growth.